Incidence and trends of central line associated pneumothorax using radiograph report text search versus administrative database codes. Issue 12 (25th May 2018) - Reeson, Marc; Forster, Alan; van Walraven, Carl
Abstract : Background: Central line associated pneumothorax (CLAP) could be a good quality of care indicator because they are objectively measured, clearly undesirable and possibly avoidable. We measured the incidence and trends of CLAP using radiograph report text search with manual review and compared them with measures using routinely collected health administrative data. Methods: For each hospitalisation to a tertiary care teaching hospital between 2002 and 2015, we searched all chest radiography reports for a central line with a sensitive computer algorithm. Screen positive reports were manually reviewed to confirm central lines. The index and subsequent chest radiography reports were screened for pneumothorax followed by manual confirmation. Diagnostic and procedural codes were used to identify CLAP in administrative data. Results: In 685 044 hospitalisations, 10 819 underwent central line insertion (1.6%) with CLAP occurring 181 times (1.7%). CLAP risk did not change over time. Codes for CLAP were inaccurate (sensitivity 13.8%, positive predictive value 6.6%). However, overall code-based CLAP risk (1.8%) was almost identical to actual values possibly because patient strata with inflated CLAP risk were balanced by more common strata having underestimated CLAP risk. Code-based methods inflated central line incidence 2.2 times and erroneously concluded that CLAP risk decreased significantly over time. Conclusions: Using valid methods, CLAP incidence was similar to those in the literature but has not changed over time. Although administrative database codes for CLAP were very inaccurate, they generated CLAP risks very similar to actual values because of offsetting errors. In contrast to those from radiograph report text search with manual review, CLAP trends decreased significantly using administrative data. Hospital CLAP risk should not be measured using administrative data.